2018
DOI: 10.1007/s12264-018-0217-7
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D4 Receptor Gene Associated with the Frontal-Striatal-Cerebellar Loop in Children with ADHD: A Resting-State fMRI Study

Abstract: Attention deficit hyperactivity disorder (ADHD) is a common childhood neuropsychiatric disorder that has been linked to the dopaminergic system. This study aimed to investigate the effects of regulation of the dopamine D4 receptor (DRD4) on functional brain activity during the resting state in ADHD children using the methods of regional homogeneity (ReHo) and functional connectivity (FC). Resting-state functional magnetic resonance imaging data were analyzed in 49 children with ADHD. All participants were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 62 publications
(65 reference statements)
1
34
0
Order By: Relevance
“…In Wang, Hu, Yao, & Jackson’s work (2013), researchers found the right rectus gyrus showed increased amplitude of low frequency fluctuation (ALFF) in ADHD patients. In another study, researchers reported increased FC in rectus gyrus for ADHD patients with DRD2 2R allele (Qian et al, 2018). Taken together, these findings suggested that abnormal activities of the superior frontal gyrus (medial) and rectus gyrus may represent a promising biomarker of ADHD.…”
Section: Discussionmentioning
confidence: 95%
“…In Wang, Hu, Yao, & Jackson’s work (2013), researchers found the right rectus gyrus showed increased amplitude of low frequency fluctuation (ALFF) in ADHD patients. In another study, researchers reported increased FC in rectus gyrus for ADHD patients with DRD2 2R allele (Qian et al, 2018). Taken together, these findings suggested that abnormal activities of the superior frontal gyrus (medial) and rectus gyrus may represent a promising biomarker of ADHD.…”
Section: Discussionmentioning
confidence: 95%
“…Early radiological approaches with increasingly detailed analysis of inflammatory or degenerative processes of the cerebellum in more recent years included [ 18 F] FDG [ 2 , 17 , 147 , 148 , 149 ] and 15 O measurements or MRI methods [ 17 , 26 , 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular/genetic studies are performed focusing on a dopaminergic gene, which supports the evident role of dopamine in the pathophysiology of ADHD (Qian et al., 2018; van der Voet et al., 2016). Apart from all studies published in association with genetic factors, no DNA variants have been indisputably demonstrated as contributing to ADHD vulnerability.…”
Section: Pathophysiologymentioning
confidence: 92%